Mother’s Education and Students’ Multiple Intelligences - Shahzada, Gulap (Richtmann Publishing, 2011)
The main objective of the study was to find out the relationship between mother’s education and students’ multiple intelligences.Pearson Coefficient Correlation was used to find out the relationship between mother’s education and students’ multiple intelligences. Asignificant correlation was found between mother’s education and students’ verbal/linguistic, logical/mathematical and musicalintelligence. An insignificant correlation was found between mother’s education and students’ visual/spatial, bodily/kinesthetic,interpersonal, intrapersonal and naturalistic intelligence. It was recommended that children should be provided various opportunities sothey may enhance their different types of intelligence.